THE IMPACT OF ENTERPRISE RESOURCE PLANNING (ERP) SYSTEMS ON ACHIEVING THE EFFECTIVENESS OF INTERNAL CONTROL FOR COMPANIES CASE STUDY (GENERAL MOTORS) (World Economics and Finance Bulletin, 2023)
Internal control is crucial for promoting good governance, ensuring compliance with regulations, fostering transparency, safeguarding assets, improving financial reporting, and enhancing risk management. ERP systems are essential for companies as they improve operational efficiency, enhance data visibility, promote collaboration, enhance customer service, optimize financial management, and provide scalability to meet evolving business needs. Leveraging an ERP system enables companies to streamline operations, reduce costs, and enhance overall performance. ERP systems also contribute to internal control effectiveness by providing access controls, automating processes, ensuring data accuracy, enabling real-time monitoring, and maintaining audit trails. In the case of General Motors (GM), the utilization of the SAP ERP system facilitates the management of financial transactions and reporting. Internal control leverages the ERP system for real-time monitoring, ensuring compliance with accounting standards and regulations, identifying control issues, and supporting data accuracy. By leveraging the ERP system, GM enhances the accuracy and efficiency of its internal control processes, particularly for digital financial statements.